2005
DOI: 10.1111/j.1468-1331.2005.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

A role of TNF‐α gene variant on juvenile ischemic stroke: a case–control study

Abstract: The role of genetic factors in the individual predisposition to develop ischemic stroke has been assessed by previous studies performed both in animal models and in humans. The main goal of the current investigation was to determine the possible contribution of genes encoding procoagulant and inflammatory factors on the occurrence of ischemic stroke in a cohort of young cases and corresponding controls. One hundred and fifteen cases of ischemic stroke were recruited for this study. A detailed clinical assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…The relevance of these experimental findings was extended to a human cohort of early‐onset ischemic stroke cases. This population was previously investigated for polymorphisms of candidate genes encoding procoagulant and inflammatory factors and methionine metabolism components: for a polymorphism of type C natriuretic peptide receptor (NPR3) promoter gene and for polymorphisms of chromosome 12p13 25, 26, 27, 28. In this population, an SNP study revealed a significant association between an intronic marker (rs11237379) of NDUFC2 and early‐onset ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of these experimental findings was extended to a human cohort of early‐onset ischemic stroke cases. This population was previously investigated for polymorphisms of candidate genes encoding procoagulant and inflammatory factors and methionine metabolism components: for a polymorphism of type C natriuretic peptide receptor (NPR3) promoter gene and for polymorphisms of chromosome 12p13 25, 26, 27, 28. In this population, an SNP study revealed a significant association between an intronic marker (rs11237379) of NDUFC2 and early‐onset ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented a TNF(Ϫ308) allelic association with ischemic stroke, but the results have not been consistent across populations. Whereas the TNF(Ϫ308)A allele was found to be protective in Korean adults with ischemic stroke 15 and patients with lacunar infarcts, 16 it conferred an increased risk of ischemic stroke in younger Italian patients 17 and patients with a preceding febrile episode. 18 Another study in Turkish children found no association between the TNF(Ϫ308) SNP and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response associated with the ischemic injury can be influenced by functional polymorphisms in components of the immune system and consequently the final cerebral ischemic burden [2,3,4]. Recent reports suggested that promoter region polymorphism in the tumor necrosis factor-α (TNF-α) gene at position –308 is an important risk factor for large-vessel stroke in children with SCA [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%